Mishmi-land musings - Edited by Arup Kumar Dutta (Tezu Lohit Youth Library Network, 2017)
This book is a justification of the need to promote focused education of adolescent girls, from the rural and marginalised communities.
An anthology of creative writings by Lohit Youth Library reader-activists published in different children's magazines from 2010-16
Keywords: Children education